1999
DOI: 10.3354/meps187031
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between glass fiber and membrane filters for the estimation of phytoplankton POC and DOC production

Abstract: We tested the performance of 2 types of glass fiber filters (GF/F: 0.7 pm; GF/C: 1.2 pm) and 2 membrane filters (PC0.2: polycarbonate 0.2 p; CE0.22: mixed cellulose esters 0.22 pm) in estimating chlorophyll a and primary production with the 14C technique. Four experiments were carried out with water samples from the NW Mediterranean, the NE Atlantic and the Antarctic Ocean. The first experiment compared measurements of particulate organic carbon (POC) production whereas the other 3 also considered total (TOC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
7
45
0
Order By: Relevance
“…The filtrate was used to determine DPP following the same procedure as TPP. The problem of a possible adsorption of dissolved carbon on GF/F filter has been previously raised (Morán et al 1999), but Renaud et al (2005) recently demonstrated that such an artifact was not relevant in the present type of study. Scintillation vials were counted in a Packard Scintillation Counter (TriCarb 1600) and corrected for background and quenching, and results are given in mg C m -3 h -1 .…”
Section: Methodsmentioning
confidence: 78%
“…The filtrate was used to determine DPP following the same procedure as TPP. The problem of a possible adsorption of dissolved carbon on GF/F filter has been previously raised (Morán et al 1999), but Renaud et al (2005) recently demonstrated that such an artifact was not relevant in the present type of study. Scintillation vials were counted in a Packard Scintillation Counter (TriCarb 1600) and corrected for background and quenching, and results are given in mg C m -3 h -1 .…”
Section: Methodsmentioning
confidence: 78%
“…Unassimilated radioactive inorganic carbon is driven off the samples by acidification and the amount of radioactive carbon incorporated into the DPP and PPP is counted and used to calculate PER (Hellebust, 1965;Morán et al, 2006). Sources of error in this technique include the transformation of PPP to DPP through cell lysis during filtration (Sharp, 1977) and the binding of DOM to the filters (Karl et al, 1998;Morán et al, 1999).…”
Section: Production Rates Of Dom By Phytoplanktonmentioning
confidence: 99%
“…However, after the discovery of photoautotrophers smaller than 1 µm, such as cyanobacteria (Waterbury et al, 1979) and picoeukaryotes (Johnson & Sieburth, 1982), membrane filters of varied composition and smaller nominal pore size (0.22 or 0.10 µm) have been suggested in order to retain these organisms (Li et al, 1983;Platt et al, 1983). Many comparisons between glass fiber and membrane filters for several kinds of analyses, such as seston, POC, primary production by 14 C method and also pigments have been carried out (Sheldon, 1972;Holm-Hansen & Reimann, 1978;Phinney & Yentsch, 1985;Morán et al, 1999;Ashimoto & Hiomoto, 2000). Morán et al (1999) compared the filters GF/C (1.2 µm), GF/F (0.7 µm), polycarbonate (0.2 µm) and cellulose esters (0.22 µm) using natural samples and verified no significant differences among these filters in terms of Chl-a retention, since flow cytometry analyses showed that most cells were larger than 1 µm.…”
Section: Flávia M P Saldanha-corrêa* Sônia M F Gianesella and Josémentioning
confidence: 99%
“…Many comparisons between glass fiber and membrane filters for several kinds of analyses, such as seston, POC, primary production by 14 C method and also pigments have been carried out (Sheldon, 1972;Holm-Hansen & Reimann, 1978;Phinney & Yentsch, 1985;Morán et al, 1999;Ashimoto & Hiomoto, 2000). Morán et al (1999) compared the filters GF/C (1.2 µm), GF/F (0.7 µm), polycarbonate (0.2 µm) and cellulose esters (0.22 µm) using natural samples and verified no significant differences among these filters in terms of Chl-a retention, since flow cytometry analyses showed that most cells were larger than 1 µm. But these authors discuss that this result could be different if picoplankton had contributed in a large fraction in those samples.…”
Section: Flávia M P Saldanha-corrêa* Sônia M F Gianesella and Josémentioning
confidence: 99%
See 1 more Smart Citation